AN EMPRICAL STUDY ON CONSUMERS ADOPTION OF MOBILE WALLET WITH SPECIAL REFERENCE TO CHENNAI CITY - Manikandan, S.; Jayakodi, J.Mary (International Journal of Research -GRANTHAALAYAH, 2017)
In present world smart phones play an important role in the daily life of people. The technological advancement has made smartphone as devices were the mobile users can make money transaction or payment by using application installed in phone. The present study aims to explain the application and usage of wallet money endorsed by different companies and various factors that affect the consumer’s decision to adopt mobile wallet and various risks and challenges faced by the users of mobile wallet. A structured questionnaire was prepared and data were collected from 150 respondents and factors affecting the adoption and usage of mobile wallet was analysed by using ANOVA to get the statistical result from data collected.